Strategic management of IT practices in tourism for operation and service enhancement - Juan Luis Rubio Sánchez; Raquel García Revilla; Olga Martínez Moure (Administrative Sciences, 2023)
The information technology infrastructure library (ITIL) standard describes processes that should be implemented in Information Technology (IT) departments for proper operations management, which includes human resources management, economic management, and strategic management, among others. This should be especially considered in the business management of industries with no relation to information technologies (IT), such as tourism and hospitality companies. This work aims to present a method to establish the order of adoption of the IT management processes in companies that belong to the tourism industry. We conducted a survey to obtain the necessary data and developed a methodology that is based on an optimization procedure. This procedure generates the optimal sequence of IT tasks to adopt in a generic small company in the tourism industry. The methodology was then applied to a representative tourism company. Through the sequence obtained, it is shown that it is necessary to implement operative processes, and subsequently, strategic processes. A comparative study was developed to find the differences with other authors' proposals. The most important result we found was the possibility of efficient use of organizations' information to build an optimized list of IT procedures to improve their administration. The obtained list of processes is specific for each organization, and not dependent on the solutions offered by other authors who proposed a general or underoptimal list of processes.
Keywords: 350; business information; IT service administration; optimization